2017
DOI: 10.1590/1981-52712015v41n1rb20140171
|View full text |Cite
|
Sign up to set email alerts
|

Supervisão Docente Indireta: Percepções das Pacientes em Ambulatórios de Obstetrícia e Pediatria

Abstract: II PALAVRAS-CHAVE-Educação Médica.-Atendimento Ambulatorial.-Percepção.-Pacientes.-Supervisão Docente. RESUMO KEYWORDS-Medical Education.-Outpatient.-Perceptions.-Patients.-Faculty Supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In the PMM, the municipalities had the counterpart to guarantee the doctors' housing, food and travel; to implement or support family and community medicine residency programs and ensure that the professionals had the necessary time for improvement activities 6 . Studies have shown that the possibility of continuing training, as well as the availability of time for studies to keep the knowledge related to the area updated, are factors that have strongly contributed to the retention of health professionals in remote areas 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PMM, the municipalities had the counterpart to guarantee the doctors' housing, food and travel; to implement or support family and community medicine residency programs and ensure that the professionals had the necessary time for improvement activities 6 . Studies have shown that the possibility of continuing training, as well as the availability of time for studies to keep the knowledge related to the area updated, are factors that have strongly contributed to the retention of health professionals in remote areas 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…A positive perception of academic supervision was observed, as a formative process that uses the dialogical approach to carry out the synthesis between theory and practice, allowing a reflective praxis, which makes it possible to improve the performance in PHC. The power of supervision lies in stimulating the search for new knowledge 31,32 through problematizations, based on the concrete reality 16,17 , which presents increasing complexity in PHC due to the deterioration of the population' s quality of life in recent years as a result of the economic recession 33 .…”
Section: Discussionmentioning
confidence: 99%